DNA damage repair and survival outcomes in advanced gastric cancer patients treated with first‐line chemotherapy. Issue 11 (11th March 2017) - Ronchetti, Livia; Melucci, Elisa; De Nicola, Francesca; Goeman, Frauke; Casini, Beatrice; Sperati, Francesca; Pallocca, Matteo; Terrenato, Irene; Pizzuti, Laura; Vici, Patrizia; Sergi, Domenico; Di Lauro, Luigi; et al.
Abstract : The DNA damage response (DDR) network is exploited by cancer cells to withstand chemotherapy. Gastric cancer (GC) carries deregulation of the DDR and harbors genetic defects that fuel its activation. The ATM‐Chk2 and ATR‐Chk1‐Wee1 axes are deputed to initiate DNA repair. Overactivation of these pathways in cancer cells may represent an adaptive response for compensating genetic defects deregulating G1 ‐S transition ( e.g ., TP53 ) and ATM/ATR‐initiated DNA repair ( e.g ., ARID1A ). We hypothesized that DDR‐linked biomarkers may predict clinical outcomes in GC patients treated with chemotherapy. Immunohistochemical assessment of DDR kinases (pATM, pChk2, pChk1 and pWee1) and DNA damage markers (γ‐H2AX and pRPA32) was performed in biological samples from 110 advanced GC patients treated with first‐line chemotherapy, either in phase II trials or in routine clinical practice. In 90 patients, this characterization was integrated with targeted ultra‐deep sequencing for evaluating the mutational status of TP53 and ARID1A . We recorded a positive association between the investigated biomarkers. The combination of two biomarkers (γ‐H2AX high /pATM high ) was an adverse factor for both progression‐free survival (multivariate Cox: HR 2.23, 95%CI: 1.47–3.40) and overall survival (multivariate Cox: HR: 2.07, 95%CI: 1.20–3.58). The relationship between the γ‐H2AX high /pATM high model and progression‐free survival was consistent across the different TP53 backgrounds and was maintained in the ARID1A wild‐type setting. Conversely, this association was no longer observed in an ARID1A ‐mutated subgroup. The γ‐H2AX high /pATM high model negatively impacted survival outcomes in GC patients treated with chemotherapy. The mutational status of ARID1A, but apparently not TP53 mutations, affects its predictive significance. Abstract : What's new? Gastric cancer patients with activation of DNA damage repair mechanisms fare worse than those without, new results show. Cancer cells can take over DNA damage repair machinery to protect themselves from chemotherapy. These authors speculated that biomarkers related to DDR might predict clinical outcomes. To find out, they tested samples from 110 gastric cancer patients for the biomarkers and also for a couple of telltale genetic mutations. Patients with biomarkers indicating DDR activation had worse progression‐free survival than those without, but this relationship disappeared in the presence of a defective ARID1A gene, which hinders DDR initiation.